Analysis of Carrying Capacity and Population Food Balance of Drought - Prone Tahsils in Jalgaon District, Maharashtra - Patil, Namdeo Arjun; Suryawanshi, D. Shivaji; Kate, Asha M. (National Geographical Journal of India, 2022)
The idea of carrying capacity of land is closely related to sustainable development, because both refer to the need for survival rather than capital. However, in future, it is recommended to bring down the population pressure so as to avoid any decline in the carrying capacity of the land. The analysis of carrying capacity of land, and population food balance in drought- prone Tahsils in Jalgaon district is an attempt to understand the man and land relationship. The carrying capacity of agricultural land is worked out by applying Jasbir Singh, (1972) using secondary data of population and cropping data of 9 tahsils of 31 years collected from Census Handbook of Jalgaon district. This study helps in finding out the relative population pressure on the available arable land in different tahsils of the study region. The increasing pressure of population on the available resources is a matter of great concern to the present academicians, planners and policy makers. Geographers are spatially and temporarily concerned with deteriorating man and land relationship (Gharge, 2011). The results of the present study indicate that the carrying capacity of land is 1231 persons / sq.km and food crop density is 1062 persons / sq.km.